118k views
5 votes
5y + 7 = 3y + 1

HELLLP

User Darem
by
5.9k points

2 Answers

6 votes

Answer:

y = -3

Explanation:

5y = 3y - 6

2y = -6

y = -3

User Grant Zhu
by
5.3k points
5 votes

To get the variable on one side, first subtract 7 from both sides. This equals:

5y = 3y -6

Then, subtract 3y from both sides. This equals:

2y = -6

Finally, divide both sides by 2 so the variable is by itself. This equals:

y = -3

That is the final answer. If you need more help, comment below and I will do my best.

User Artjom
by
5.3k points